2009
DOI: 10.1158/1078-0432.ccr-08-2257
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gene Expression Predicting Local Control in Cervical Cancer: Results from Radiation Therapy Oncology Group 0128

Abstract: Purpose:To evaluate the potential of gene expression signatures to predict response to treatment in locally advanced cervical cancer treated with definitive chemotherapy and radiation. Experimental Design: Tissue biopsies were collected from patients participating in Radiation Therapy Oncology Group (RTOG) 0128, a phase II trial evaluating the benefit of celecoxib in addition to cisplatin chemotherapy and radiation for locally advanced cervical cancer. Gene expression profiling was done and signatures of pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…[35][36][37] Additionally, whole transcriptomic RNA-seq analysis was performed, providing a more robust and in-depth characterization of gene expression compared to targeted microarray analysis. Analyzing tumor gene expression before and 3 weeks into CRT provides novel insight into treatment response and offers advantages to analyzing one time point alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] Additionally, whole transcriptomic RNA-seq analysis was performed, providing a more robust and in-depth characterization of gene expression compared to targeted microarray analysis. Analyzing tumor gene expression before and 3 weeks into CRT provides novel insight into treatment response and offers advantages to analyzing one time point alone.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Inclusion in our RNA-seq study mandated the presence of neoplastic cells in cervical tissue 3 weeks into CRT, thus a valid concern is that our study is biased towards tumors that are inherently resistant to treatment. Though we likely could have included more patients had we studied an earlier time point, evaluating gene expression 3 weeks into treatment allows for unique insight into a patient's response to radiation therapy compared to analysis after only a few fractions of radiation, which the existing prior studies have done.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a microarray study identified TRIP6 as one of seven top‐ranked transcripts overexpressed in highly metastatic and therapy‐resistant cervical cancers (Weidhaas et al, 2009). Furthermore, a recent genome‐wide screen identified another hitherto unknown TRIP6 splice variant, which retains its last intron, to be induced in HER2/neu (v‐erb‐b2 erythroblastic leukaemia viral oncogene homologue 2)‐expressing breast cancers, suggesting a possible involvement of TRIP6 in HER2/neu‐mediated tumorigenesis and invasiveness (Ferreira et al, 2010).…”
Section: The Roles Of Trip6 In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
“…27,28 Additionally, using the differential gene expression signatures between the original biopsy and the biopsy at the initial implant, a 7-gene signature panel was identified that could predict outcome in advanced cervical cancer patients from 0128. 29 Immunohistochemistry (IHC) is a powerful technique for measuring protein expression and correlating clinical end points for well-annotated samples in RTOG studies. In 51 patients from RTOG 0116 and 0128, subunit expression of ribonucleotide reductase by IHC was prognostic in nodepositive patients.…”
Section: Translational Studiesmentioning
confidence: 99%